TEKNIK ATMOSFIR TERMODIFIKASI DALAM PENANGANAN BUAH DAN SAYUR SEGAR - Nur Kusuma Dewi (MEDIAGRO, 2007)
Fruits and vegetable are spoiled easily commoditie. It is because the activity of metabolism that still moved on after picking.  The low temperatur storage is one of alternative solution, but it hasn’t the best, so it is combined with modificated atmosphere storage.      The principle of this way is change the compotisition normal atmosphere with increase carbondioxide (CO2)  concentration   and decrease oxigene (O2) concentration. In the modificated atmosphere technique application is done by using designed polyback,  so in this package will be created a atmosphere condition that appopriate with fruits and vegetables which will be storaged in low temperature. Therefore it will increase the saving time of fruits and vegetables,  so they can be consumed in the fresh condition Key word:  Atmosphere,   modificated,  Fruits , Vegetables